The Analysis of Associative Meaning on the Poems Written by Maya Angelou - Arpin, Ni Putu Raka L.; Erfiani, Ni Made Diana; Wardhana, I Gede Neil P. (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2024)
This study is entitled â€œThe Analysis of Associative Meaning on the Poems Written by Maya Angelouâ€. The aims of this study are to identify and explain the types of associative meaning and also describe the function of associative meaning that found on the Maya Angelouâ€™s poem. This study used descriptive qualitative method to analyze the data and used theory purposed by Leech (1981) for the types of associative meaning and Searle (1979) as well for the functions of associative meaning. This study are used three collection poem by Maya Angelouâ€™s poem, there are: Caged Bird, Phenomenal Woman, and Still I Rise poem. The result of the study showed that found on the Maya Angelouâ€™s poem, there are: five types of associative meaning that found in the poems, there are 14 data of connotative meaning, 5 data of social meaning, 8 data of affective meaning, 3 data of reflected meaning and 3 data of collocative meaning and 2) four of five functions of associative meaning that found in this study, there are 18 data of assertive, 2 data of commissive, 9 data of expressive, and 1 data of declaratives but also no directives functions data that found in the poems.